Location matters: distinct DNA methylation patterns in GABAergic interneuronal populations from separate microcircuits within the human hippocampus - Ruzicka, W Brad (Hum Mol Genet, 2018)
Recent studies describe distinct DNA methylomes among phenotypic subclasses of neurons in the human brain, but variation in DNA methylation between common neuronal phenotypes distinguished by their function within distinct neural circuits remains an unexplored concept. Studies able to resolve epigenetic profiles at the level of microcircuits are needed to illuminate chromatin dynamics in the regulation of specific neuronal populations and circuits mediating normal and abnormal behaviors. The Illumina HumanMethylation450 BeadChip was used to assess genome-wide DNA methylation in stratum oriens GABAergic interneurons sampled by laser-microdissection from two discrete microcircuits along the trisynaptic pathway in postmortem human hippocampus from eight control, eight schizophrenia, and eight bipolar disorder subjects. Data were analysed using the minfi Bioconductor package in R software version 3.3.2. We identified 11 highly significant differentially methylated regions associated with a group of genes with high construct-validity, including multiple zinc finger of the cerebellum gene family members and WNT signaling factors. Genomic locations of differentially methylated regions were highly similar between diagnostic categories, with a greater number of differentially methylated individual cytosine residues between circuit locations in bipolar disorder cases than in schizophrenia or control (42, 7, and 7 differentially methylated positions, respectively). These findings identify distinct DNA methylomes among phenotypically similar populations of GABAergic interneurons functioning within separate hippocampal subfields. These data compliment recent studies describing diverse epigenotypes among separate neuronal subclasses, extending this concept to distinct epigenotypes within similar neuronal phenotypes from separate microcircuits within the human brain.